A mammoth mystery - Stilton, Geronimo (Stilton, Geronimo. Cavemice, 2017)
The cavemice cannot make mammoth milkshakes--their national drink--because all of the mammoths have fled Old Mouse City, so Geronimo Stiltonoot embarks on a journey to find the beasts.